Durable Effect of Pyrotinib and Metronomic Vinorelbine in HER2-Positive Breast Cancer With Leptomeningeal Disease: A Case Report and Literature Review - Chi, Yajing; Shang, Mao; Xu, Liang; Gong, Heyi; Tao, Rongjie; Song, Lihua; Zhang, Baoxuan; Yin, Sha; Cong, Binbin; Li, Huihui (Frontiers in Oncology, 2022)
Leptomeningeal metastases (LM) are rare and catastrophic for metastatic breast cancer (MBC). The prognosis of HER2-positive breast cancer (BC) with LM is extremely poor. There is no high-quality evidence of treatment regimens in HER2-positive BC with LM yet. Here, we present a case of LM in a 50-year-old woman with HER2-positive BC. Immunohistochemistry revealed invasive ductal carcinoma, estrogen receptor negative, progesterone receptor negative, HER2 3+, P53 positive 80%, and Ki-67 positive 35%. Reported for the first time, the patient was given pyrotinib-targeted therapy (400 mg, oral, every day), metronomic vinorelbine (40 mg, oral, three times a week), and intrathecal methotrexate (10 mg, infrequent and irregular use due to poor compliance) synchronously. The patient received and benefited from the treatment regimen for 16 months. And the quality of life, as self-reported, improved significantly. We also comprehensively summarized all the case reports, observational studies, and clinical trials related to HER2-positive BC with LM in the PubMed database and ClinicalTrials.gov. Intrathecal chemotherapy (methotrexate, cytarabine, thiotepa), intrathecal trastuzumab, whole-brain radiotherapy, and systemic therapy are commonly used treatment options according to a review of the literature and research. Pembrolizumab and trastuzumab deruxtecan (DS-8201) as novel drugs are promising in LM. Furthermore, trastuzumab emtansine (T-DM1) and tyrosine kinase inhibitors (TKIs) such as tucatinib and neratinib have exhibited good efficacy in HER2-positive BC with central nervous system (CNS) metastases and deserve further exploration. In our report, combining pyrotinib-targeted therapy with metronomic chemotherapy is a potential regimen, which has presented satisfactory therapeutic efficacy and also warrants additional investigation in HER2-positive BC with LM.